1999
DOI: 10.1055/s-2006-960444
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis and Antimicrobial Activity of the Resin Ladano, of its Essential Oil and of the Isolated Compounds**

Abstract: Fractionation of the resin Ladano from Cistus creticus subsp. creticus and susceptibility testing using the chromatographic fractions showed that its antistaphylococcal activity was mainly due to the diterpene sclareol. The antimicrobial activity of its essential oil, of the chromatographic fractions, and of the isolated compounds was also evaluated against Staphylococcus aureus, Staphylococcus epidermidis, and Staphylococcus hominis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 1 publication
1
46
0
5
Order By: Relevance
“…Sclareol induces apoptosis in human leukemia cell lines, via an interesting mechanism that down-regulates c-myc without affecting the expression of the anti-apoptotic protein, Bcl-2 [9], and in cells derived from solid tumors by a mechanism that appears to be independent on p53-expression [12]. Further, in a preliminary study we have shown that sclareol possesses a modest anticancer activity in a human colon cancer xenograft/mouse model, when this compound is administered in an encapsulated (liposomal) form, as this was concluded calculating the doubling time of tumors from 200 to 400 mm 3 [13]. Our choice of liposomes as lipid-based drug carriers to deliver sclareol was motivated by their well documented ability to deliver bioactive compounds in a targeted manner, and their favourable physicochemical properties that typically result in improvement of the pharmacokinetic properties and pharmacological response of the encapsulated drugs, while reducing drug-associated side effects (for recent reviews, see refs.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Sclareol induces apoptosis in human leukemia cell lines, via an interesting mechanism that down-regulates c-myc without affecting the expression of the anti-apoptotic protein, Bcl-2 [9], and in cells derived from solid tumors by a mechanism that appears to be independent on p53-expression [12]. Further, in a preliminary study we have shown that sclareol possesses a modest anticancer activity in a human colon cancer xenograft/mouse model, when this compound is administered in an encapsulated (liposomal) form, as this was concluded calculating the doubling time of tumors from 200 to 400 mm 3 [13]. Our choice of liposomes as lipid-based drug carriers to deliver sclareol was motivated by their well documented ability to deliver bioactive compounds in a targeted manner, and their favourable physicochemical properties that typically result in improvement of the pharmacokinetic properties and pharmacological response of the encapsulated drugs, while reducing drug-associated side effects (for recent reviews, see refs.…”
Section: Introductionmentioning
confidence: 79%
“…Labdane diterpenes abundant in several families of plants and algae possess a labdane skeleton consisting of a decalin system and a C-6 ring, which may be open or closed with an oxygen atom, as in manoyl oxide and its derivatives [2,3]. Of special interest among these compounds that exhibit a variety of activities [4] is forskolin, a manoyl oxide derivative that can activate adenylate cyclase by directly interacting with the catalytic subunit or a closely associated protein of the adenylate cyclase system [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several flavonoid aglycons were isolated and studied from the genus Cistus, the members of which have predominant habitats in the Mediterranean region [4]. In the recent years our laboratory contributed in the chemical and pharmacological investigation of Cistus, a genus found in Spain, Greece, Cyprus and geographic areas located between Morocco and Tunisia [5][6][7][8][9]. We have also performed comparison studies of active and inactive membrane perturbing compounds of natural origin using various biophysical methods [10].…”
Section: Introductionmentioning
confidence: 99%
“…A number of essential oils and their isolated individual components exhibit antimicrobial activity (Fernandez-Ocana et al, 2004;Stoyanova et al, 2006;Al-Bayati, 2009;Demetzos et al, 1999). The phenolic components are most active and appear to act principally as membrane permissible.…”
Section: Discussionmentioning
confidence: 99%